ENDOCRINOLOGY IN PREGNANCY: Pregnancy and the incidence, diagnosing and therapy of Graves' disease. Issue 5 (November 2016) - Laurberg, Peter; Andersen, Stine Linding
Abstract : Thyroid hormones are essential developmental factors, and Graves' disease (GD) may severely complicate a pregnancy. This review describes how pregnancy changes the risk of developing GD, how early pregnancy by several mechanisms leads to considerable changes in the results of the thyroid function tests used to diagnose hyperthyroidism, and how these changes may complicate the diagnosing of GD. Standard therapy of GD in pregnancy is anti-thyroid drugs. However, new studies have shown considerable risk of birth defects if these drugs are used in specific weeks of early pregnancy, and this should be taken into consideration when planning therapy and control of women who may in the future become pregnant. Early pregnancy is a period of major focus in GD, where pregnancy should be diagnosed as soon as possible, and where important and instant change in therapy may be warranted. Such change may be an immediate stop of anti-thyroid drug therapy in patients with a low risk of rapid relapse of hyperthyroidism, or it may be an immediate shift from methimazole/carbimazole (with risk of severe birth defects) to propylthiouracil (with less risk), or maybe to other types of therapy where no risk of birth defects have been observed. In the second half of pregnancy, an important concern is that not only the mother with GD but also her foetus should have normal thyroid function.